Reflections on Korea in 2010: Trials and prospects for recovery of common sense in 2011 - Paik Nak-chung (Japan Focus)
It seems that Korean society experienced more trials than usual in the year 2010. Perhaps it feels that way because the final weeks since the shelling of Yeongpyeong Island on the West Sea of the Korean peninsula on November 23 have been filled with events that evoke grief, anger, and anxiety.As for the Yeongpyeong incident itself, whatever its cause or justification, the fact that North Korea deliberately opened fire on South Korean territory is enough to bring shock and anger. To make matters worse, the incompetence and sloppiness of the South Korean government in its initial response caused uneasiness among the citizens, and its belated displays of toughness and escalation of tension, proclaiming "readiness for a full-scale war," has added to South Korean people's sense of insecurity and even stirred their anger.Taking advantage of the security crisis, members of the ruling Grand National Party (GNP) on December 8 unilaterally and employing physical force rammed through the National Assembly the annual budget and other disputed bills. The main reason behind this 'snatching' action apparently was to push on with the Four Great Rivers Project and to pass the related pernicious legislation known as the "Water-Friendly Region Law." We may now foresee an accelerating destruction not only of the nation's environment but of democracy and rule of law as well. In the meantime, the speedy economic recovery that the government boasts about, setting aside for the moment the view of some experts that we still have to wait and see how real the recovery is, has not succeeded in improving the livelihood of ordinary people or creating many new jobs.The author calls for fresh thinking to avert a regionwide and domestic crisis.